2022
DOI: 10.1063/5.0097795
|View full text |Cite
|
Sign up to set email alerts
|

Vertical ferroelectric thin-film transistor array with a 10-nm gate length for high-density three-dimensional memory applications

Abstract: Hafnia-based ferroelectric thin-film transistors (FeTFTs) are regarded as promising candidates for future nonvolatile memory devices owing to their low power consumption, high operational speed, and complementary metal–oxide–semiconductor compatibility. However, the scalability of hafnia-based materials and the feasibility of three-dimensional (3D) device fabrication should be confirmed for ultrahigh-density memory applications. In this work, we demonstrate that FeTFTs can be scaled down to a 10-nm dimension u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The 3D FeNAND arrays with metal-ferroelectric-semiconductor-structured memory cells were fabricated using photolithography and the lift-off method (Supplementary Fig. 1 ) 24 , 41 . First, TiN word lines (WLs) and SiO 2 layers were alternately deposited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D FeNAND arrays with metal-ferroelectric-semiconductor-structured memory cells were fabricated using photolithography and the lift-off method (Supplementary Fig. 1 ) 24 , 41 . First, TiN word lines (WLs) and SiO 2 layers were alternately deposited.…”
Section: Resultsmentioning
confidence: 99%
“…Also, ferroelectric transistors have the potential to be adopted in high-density 3D NNs due to their high scalability and CMOS-compatibility. The high scalability of hafnia-based ferroelectrics can be advantageous for 3D memory applications 40,41 . Recent research demonstrated that hafnia-based ferroelectrics could be operated with a thickness under a few nanometers [42][43][44] .…”
mentioning
confidence: 99%
“…[22,24,25,[56][57][58][59][60] Furthermore, the facile deposition of hafnia-based ferroelectrics using ALD has been used to fabricate next-generation 3D memory devices based on ferroelectric hafnia. [23,26,61,62]…”
Section: History Of Ferroelectric Memoriesmentioning
confidence: 99%
“…Due to these advantages, hafnia-based ferroelectrics have been used in next-generation memory devices (such as ferroelectric capacitors, transistors, and tunnel junctions [FTJs]). [22][23][24][25][26] This paper reviews the recent findings and applications of hafnia-based ferroelectrics, highlighting the recent advances in ferroelectric transistors for next-generation memory and neuromorphic Ferroelectric materials have been intensively investigated for highperformance nonvolatile memory devices in the past decades, owing to their nonvolatile polarization characteristics. Ferroelectric memory devices are expected to exhibit lower power consumption and higher speed than conventional memory devices.…”
mentioning
confidence: 99%
“…[7] The extremely low off-current of oxide semiconductors can improve the retention of dynamic random-access memory (DRAM) [8,9] by lowering the charge loss through the transistor, and oxide semiconductors exhibit good compatibility with various insulating layers, allowing them to be used as semiconductor materials for NAND flash [10,11] or ferroelectric random-access memory (FeRAM). [12] For these various applications of oxide semiconductors, it is important to understand the role of the elements in oxide semiconductors to optimize the characteristics of thin films and devices. In particular, the characteristics of the devices can vary dramatically depending on the ratio of the cations in the oxide semiconductors.…”
mentioning
confidence: 99%